Surprisingly Fast Interface and Elbow Angle Dynamics of Antigen-Binding Fragments - Fernández-Quintero, Monica L.; Kroell, Katharina B.; Heiss, Martin C.; Loeffler, Johannes R.; Quoika, Patrick K.; Waibl, Franz; Bujotzek, Alexander; Moessner, Ekkehard; Georges, Guy; Liedl, Klaus R. (Frontiers in Molecular Biosciences, 2020)
Antigen-binding fragments (Fabs) play a crucial role in the antigen-binding process. The Fab consists of a heavy and light chain and can be subdivided into a variable (VH and VL) and a constant region (CH and CL). The variable region contains the complementarity determining region (CDR), which is formed by six hypervariable loops, shaping the antigen binding site, the paratope. Apart from the CDR loops, both the elbow angle and the relative interdomain orientations of the VH-VL and the CH-CL domains influence the shape of the paratope. Thus, characterization of the interface and elbow angle dynamics is essential to antigen specificity. We studied nine antigen binding fragments (Fab) to investigate the influence of affinity maturation, antibody humanization and different light chain types on the interface and elbow angle dynamics. While the CDR loops reveal conformational transitions in the micro-to millisecond timescale, both the interface and elbow angle dynamics occur on the low nanosecond timescale. Upon affinity maturation we observe a substantial rigidification of the VH and VL interdomain and elbow-angle flexibility, reflected in a narrower and more distinct distribution. Antibody humanization describes the process of grafting non-human CDR loops onto a representative human framework. As the antibody framework changes upon humanization, we investigated if both the interface and the elbow angle distributions are changed or shifted. The results clearly showed a substantial shift in the relative VH-VL distributions upon antibody humanization, indicating that different frameworks, favor distinct interface orientations. Additionally, the interface and elbow angle dynamics of five antibody fragments with different light chain types are included, because of their strong differences in elbow angles. For these five examples we clearly see a high variability and flexibility in both interface and elbow angle dynamics, highlighting the fact that Fab interface orientations and elbow angles interconvert between each other in the low nanosecond timescale. Understanding, how the relative interdomain orientations and the elbow angle influence antigen specificity, affinity and stability, has broad implications in the field of antibody modelling and engineering.